2018
DOI: 10.1080/02640414.2018.1474535
|View full text |Cite
|
Sign up to set email alerts
|

Loading differences in single-leg landing in the forehand- and backhand-side courts after an overhead stroke in badminton: A novel tri-axial accelerometer research

Abstract: Anterior cruciate ligament (ACL) injuries in badminton commonly occur during single-leg landing after an overhead stroke in the backhand-side court. This study compared differences in trunk acceleration and kinematic variables during single-leg landing in the forehand- and backhand-side courts after an overhead stroke. Eighteen female junior badminton players performed two singles games while wearing a tri-axial accelerometer. The moment that over 4g of resultant acceleration was generated was determined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Athletic ability, gender, and posture are related to badminton injuries by understanding loading characteristics. For example, unskilled female players have been shown to be more vulnerable to lower extremity injuries (Lam et al, 2018), and postures have been associated with knee injuries during badminton games (Sasaki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Athletic ability, gender, and posture are related to badminton injuries by understanding loading characteristics. For example, unskilled female players have been shown to be more vulnerable to lower extremity injuries (Lam et al, 2018), and postures have been associated with knee injuries during badminton games (Sasaki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a player puts a greater force on the take-off foot to propel upward with a velocity vertical to the center of mass (9). The repeated jumps and deviations in jumping and landing techniques during the games are becoming the primary causes of muscle fatigue (23).…”
Section: Introductionmentioning
confidence: 99%
“…The use of IMUs worn on the Upper Back and Lower Back in training also had significant positive responses. The use of the IMUs worn on the upper back is common across a range of sports (Chambers et al, 2015) and has been used to assess player load in racket sports (Dieu et al, 2014;Galé-Ansodi et al, 2016;Sasaki et al, 2018;Abdullahi et al, 2019;Wylde et al, 2019). However, in a study on Badminton, a low correlation was found between loading data obtained from an upper body-mounted IMU and differential ratings of perceived exertion (RPE) at the lower limbs (Wylde et al, 2019).…”
Section: Discussionmentioning
confidence: 99%